Observation on the sediment pattern using sediment river study model with the presence of rainfall - Nur Raihan , Yaakob (2014)
Sediment can be categorized as loose sand, clay, silt and other soil particles that are settled down at the bottom of a water body. Sedimentation process is a process where sediment is being transported away from its original location and deposited to another place. Sedimentation process can cause harm if it does not being controlled properly. Excessive capacity of sediment can caused reduction in water storage capacity in a reservoir, collapsing a bridge, forming a sediment dam in a river and other disaster. However, the presence of rainfall can affect the sedimentation process by increasing the volume and velocity of the water in the river; meaning that it can doubled up the impact of sedimentation. This shows on how important it is to have a great understanding regarding to the sediment. In this study, the observation on the sediment pattern is done by using a 11 Ox45x25 cm of river model with several physical features of river, presence of rainfall and sediment is being made. The purposes of the study are to understand better about both of sediment and its process. Three set of experiment is done by considering the location of the rainfall. The velocity of river flow and rainfall intensity; which are 0.35 m/s and 0.16 us respectively, is being fixed in order to distinguish the result. The sediment deposited along the river model and created a pattern. In order to recognize the pattern, the result is represented in a chart rate of sediment size distribution rate at five point of location along the river model. As the overview of the result, the pattern of sediment is differ due to the river features. Based on the analysis generated from the experimental result, it can be concluded that the presence of rainfall will increase the river discharged and hence, making the velocity and the flow rate of the river increased. The sediment pattern will be affected by the river changes. The presence of rainfall did affect the sedimentation in the matter of sediment quantity. This shows that rainfall can be another factor that promotes sedimentation.